Searching for stable fullerenes in space with computational chemistry. Issue 1 (13th February 2019) - Candian, Alessandra; Gomes Rachid, Marina; MacIsaac, Heather; Staroverov, Viktor N; Peeters, Els; Cami, Jan
Abstract: We report a computational study of the stability and infrared (IR) vibrational spectra of neutral and singly ionized fullerene cages containing between 44 and 70 carbon atoms. The stability is characterized in terms of the standard enthalpy of formation per CC bond, the HOMO–LUMO gap, and the energy required to eliminate a C2 fragment. We compare the simulated IR spectra of these fullerene species to the observed emission spectra of several planetary nebulae (Tc 1, SMP SMC 16, and SMP LMC 56) where strong C60  emission has been detected. Although we could not conclusively identify fullerenes other than C60 and C70, our results point to the possible presence of smaller (44, 50, and 56-atom) cages in those astronomical objects. Observational confirmation of our prediction should become possible when the James Webb Space Telescope comes online.